Hyperpolarized 13C‐lactate to 13C‐bicarbonate ratio as a biomarker for monitoring the acute response of anti‐vascular endothelial growth factor (anti‐VEGF) treatment. (14th March 2016) - Park, Jae Mo; Spielman, Daniel M.; Josan, Sonal; Jang, Taichang; Merchant, Milton; Hurd, Ralph E.; Mayer, Dirk; Recht, Lawrence D.
Abstract : Hyperpolarized [1‐ 13 C]pyruvate MRS provides a unique imaging opportunity to study the reaction kinetics and enzyme activities of in vivo metabolism because of its favorable imaging characteristics and critical position in the cellular metabolic pathway, where it can either be reduced to lactate (reflecting glycolysis) or converted to acetyl‐coenzyme A and bicarbonate (reflecting oxidative phosphorylation). Cancer tissue metabolism is altered in such a way as to result in a relative preponderance of glycolysis relative to oxidative phosphorylation (i.e. Warburg effect). Although there is a strong theoretical basis for presuming that readjustment of the metabolic balance towards normal could alter tumor growth, a robust noninvasive in vivo tool with which to measure the balance between these two metabolic processes has yet to be developed. Until recently, hyperpolarized 13 C‐pyruvate imaging studies had focused solely on [1‐ 13 C]lactate production because of its strong signal. However, without a concomitant measure of pyruvate entry into the mitochondria, the lactate signal provides no information on the balance between the glycolytic and oxidative metabolic pathways. Consistent measurement of 13 C‐bicarbonate in cancer tissue, which does provide such information, has proven difficult, however. In this study, we report the reliable measurement of 13 C‐bicarbonate production in both the healthy brain and a highly glycolytic experimental glioblastoma model using an optimized 13 C MRS imaging protocol. With the capacity to obtain signal in all tumors, we also confirm for the first time that the ratio of 13 C‐lactate to 13 C‐bicarbonate provides a more robust metric relative to 13 C‐lactate for the assessment of the metabolic effects of anti‐angiogenic therapy. Our data suggest a potential application of this ratio as an early biomarker to assess therapeutic effectiveness. Furthermore, although further study is needed, the results suggest that anti‐angiogenic treatment results in a rapid normalization in the relative tissue utilization of glycolytic and oxidative phosphorylation by tumor tissue. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : With the capacity to obtain the reliable measurement of 13 C‐bicarbonate and 13 C‐lactate produced from hyperpolarized [1‐ 13 C]pyruvate in brain tumors, we demonstrated that the ratio of 13 C‐lactate to 13 C‐bicarbonate provides a more robust metric than 13 C‐lactate alone for the assessment of the metabolic effects of anti‐angiogenic therapy. The acute decrease in the lactate to bicarbonate ratio in glioma after anti‐angiogenic therapy suggests a potential application for this technology as a biomarker to assess the therapeutic effectiveness at very early times after treatment administration.